Two essays on political influence and the regulation of financial markets - Eckel, Doug (Virginia Tech, 1996)
I examine two potential instances of rent-seeking in financial markets in the 1980s. In the first essay I test whether managers engage in political activity designed to influence federal regulation of the market for corporate control. In the second, I examine whether firms in the financial services sector attempt to affect bank deregulation. Using Federal Election Commission data, I find campaign contributions by corporate political action committees (PACs) are negatively related to levels of inside ownership, my main proxy for managerial vulnerability to hostile tender offers. Contribution patterns for firms with less than 20% insider ownership are relatively highly correlated, and differ from those of firms with greater than 20% inside ownership. Low inside ownership firms have slightly higher levels of contributions to legislators on particular House and Senate committees proposing relevant legislation. However, when I analyze the impact of contributions on legislator support for regulation I find no statistical support for a theory of vote-buying. I conclude that corporate political behavior is tied to levels of inside ownership, and comprises an alternate index of manager-shareholder conflict. Using a similar approach to analyse the financial services industry, I also find significant patterns in political action committee (PAC) campaign contributions for depository (commercial bank and thrift) and non-depository (brokerage and insurance) sectors of the financial services industry during the 98th Congress (1983-84). Contributions by depository firm PACs appear not only to purchase access to legislators serving on important banking committees crucial to their interests, but are also a significant determinant of votes for repealing sections of the Glass-Steagall Act. Nondepository contributions do not appear to influence votes directly, even though the brokerage and insurance sectors effectively lobbied House Banking Committee chairman Fernand St Germain to enforce the regulatory status quo. When I measure the rents at stake in the legislation using a two-factor market model event study approach, I find that the passage of legislation in the Senate had a positive affect on depository firm returns, implying the sector's lobbying effort was justified. However non-depository PACs lobbied just as extensively, and did not experience significant abnormal returns over the same event period, even though this round of deregulation should have been a zero-sum game between the affected sectors of the industry. I then measure the correlation between the market value impacts of new legislation and contribution amounts for individual firms within the sectors. I find rents are correlated with political activity, even for firms in the non-depository sectors.
URI: http://hdl.handle.net/10919/39160
Keywords: Corporate control; Financial institutions; Financial markets; Regulation

Improving the administration of justice through the implementation of third party alternative dispute resolution processes: An analysis of process productivity and disputant strategic behavior - Stanford, John D. (Ohio State University, 1996)
The institutionalization of alternative dispute resolution (ADR) processes is the most recent development in the policy effort to reform the American civil justice system. However, the research is inconclusive and contradictory on the performance of ADR processes in institutionalized settings. This study introduces a production m odel of third party dispute resolution processes to compare the performance of court annexed arbitration, judicial settlem ent conference, and trial processes. To explain the processes’ performance, a strategic behavior model of third party dispute resolution processes identifies four strategic behaviors which influences process perform ance: integrative, distributive, opportunistic, and distributive. Through conceptualization of the m odels, several hypotheses are developed. This study introduces a production m odel of third party dispute resolution processes to compare the performance of court annexed arbitration, judicial settlem ent conference, and trial processes. To explain the processes’ performance, a strategic behavior model of third party dispute resolution processes identifies four strategic behaviors which influences process perform ance: integrative, distributive, opportunistic, and distributive. Through conceptualization of the m odels, several hypotheses are developed. This study concludes that the court annexed arbitration is the best performing process. Of the various dispute, disputant, and process characteristics identified to explain process perform ance, only the disputant’s perception of process equity during the process is significant and positive. The policy inference is that policy makers can reduce disputant costs while improving delay, process equity, and satisfaction through court-annexed arbitration.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitraje; Arbitration; Mediation; Third party